THESE CALIFORNIANS ARE CONTRIBUTING THEIR NAMES, THEIR MONEY OR THEIR EFFORTS TO DEFEAT PROP. 5. (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; List of names of people who support Californians for Common Sense.